Risk Analysis of the Implementation of IPv6 Neighbor Discovery in Public Network - Supriyanto .; Iznan Hasbullah; Rajakumar Murugesan; Azlan Osman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Internet is ubiquitous, and in recent times its growth has been exponential. This rapid growth caused the depletion of the current Internet Protocol version 4 (IPv4) address, prompting IETF with the design of the new Internet Protocol version 6 (IPv6) in the 1990’s. IPv6 is the next generation of the Internet Protocol designed with much larger address space and additional functions to ease its use for the users. One of the new functions is address auto configuration of new host’s via Neighbor Discovery Protocol (NDP). However, the implementation of NDP is not without risk in terms of security. This paper analyzes the risk of NDP implementation in public network. The result shows a number of risks that appear on the implementation of NDP over a Public Network. Neighbors cannot be trusted 100%. One of them could be an attacker who may exploit the NDP message to get their own benefit. In addition the number of insiders increases time to time.